Quantitative PCR based detection system for cyanobacterial geosmin/2-methylisoborneol (2-MIB) events in drinking water sources: Current status and challenges. (1st January 2021) - Devi, Apramita; Chiu, Yi-Ting; Hsueh, Hsin-Ta; Lin, Tsair-Fuh
Highlights: An online database (CyanoGM Explorer ) for global geosmin/2-MIB events is created. Quantitative PCR (qPCR) provides rapid, reliable and early on-site detection tool. Universal primer/probe for identifying 58 available geo sequences is lacking. 2-3 out of 11 developed primer/probe sets can detect all 28 available mic sequences. Primer design/optimization, field validation and qPCR protocols are key challenges. Abstract: Taste and odor (T&O) are an important issue in drinking water, aquaculture, recreation and a few other associated industries, and cyanobacteria-relevant geosmin and 2-methylisoborneol (2-MIB) are the two most commonly detected T&O compounds worldwide. A rise in the cyanobacterial blooms and associated geosmin/2-MIB episodes due to anthropogenic activities as well as climate change has led to global concerns for drinking water quality. The increasing awareness for the safe drinking, aquaculture or recreational water systems has boost the demand for rapid, robust, on-site early detection and monitoring system for cyanobacterial geosmin/2-MIB events. In past years, research has indicated quantitative PCR (qPCR) as one of the promising tools for detection of geosmin/2-MIB episodes. It offers advantages of detecting the source organism even at very low concentrations, distinction of odor-producing cyanobacterial strains from non-producers and evaluation of odor producing potential of the cyanobacteria at much faster rates compared to conventional techniques.The present review aims at examining the current status of developed qPCR primers and probes in identifying and detecting the cyanobacterial blooms along with geosmin/2-MIB events. Among the more than 100 articles about cyanobacteria associated geosmin/2-MIB in drinking water systems published after 1990, limited reports (approx. 10 each for geosmin and 2-MIB) focused on qPCR detection and its application in the field. Based on the review of literature, a comprehensive open access global cyanobacterial geosmin/2-MIB events database (CyanoGM Explorer) is curated. It acts as a single platform to access updated information related to origin and geographical distribution of geosmin/2-MIB events, cyanobacterial producers, frequency, and techniques associated with the monitoring of the events. Although a total of 132 cyanobacterial strains from 21 genera and 72 cyanobacterial strains from 13 genera have been reported for geosmin and 2-MIB production, respectively, only 58 geosmin and 28 2-MIB synthesis regions have been assembled in the NCBI database. Based on the identity, geosmin sequences were found to be more diverse in the geosmin synthase conserved/primer design region, compared to 2-MIB synthesis region, hindering the design of universal primers/probes. Emerging technologies such as the bioelectronic nose, Surface Enhanced Raman Scattering (SERS), and nanopore sequencing are discussed for future applications in early on-site detection of geosmin/2-MIB and producers. In the end, the paper also highlights various challenges in applying qPCR as a universal system of monitoring and development of response system for geosmin/2-MIB episodes. Graphical abstract: Image, graphical abstract